Feature reassembly and meso-parameters versus interpretability: From inconsistent null subjects in L1 Hebrew to no null subjects in L2 English - Brandel, Noa (Journal of linguistics, 2025)
This paper reports the results of a cross-sectional study investigating the acquisition of the syntactic properties associated with the null subject (meso-)parameter in English as a second language (L2) among Hebrew-speaking youngsters (18-year-olds). The two languages differ concerning these properties, with Hebrew allowing null subjects and related properties (although inconsistently) and English disallowing these properties altogether. One hundred four intermediate learners and 97 English-speaker controls provided grammaticality judgments and corrections concerning constructions involving expletive and referential null subjects, post-verbal subjects, and complementizer-trace sequences. The results reveal limited evidence for transfer from the learners’ mother tongue (first language [L1]) and indicate that learners have met the native standard concerning null and post-verbal subjects. These findings support both the meso-parametric view of cross-linguistic variation and feature reassembly on functional heads in L2 acquisition, while partially rejecting the Interpretability Hypothesis. Learners nevertheless deviate from the native standard concerning complementizer-trace sequences. This finding is unaccounted for by the meso-parametric approach, feature reassembly, or interpretability, but can instead be attributed to L1 transfer. Controls also demonstrate variability concerning complementizer-trace sequences, suggesting that the performance of all participants regarding this configuration is affected by processing difficulties, lower frequency in the input, and methodological issues with the items and/or the task.